Extração de cefamicina C por sistema de duas fases aquosas e purificação por troca iônica - Brites, Luciana Machado (2013)
Cephamycin C is a β-lactam antibiotic that belongs to the cephalosporins. This antibiotic stands out from other cephalosporins because it has activity against gram-negative bacteria and for being resistent to β-lactamases produced by pathogenic microorganisms, and which represent one of the major mechanisms of bacterial resistance to β-lactam antibiotics. In view of the restricted information in the literature about the steps of the process, both from the point of view of research and of industrial production of cephamycin C, the study about its production and, consequently, the process of separation and purification becomes of great importance. Therefore, the main objective of this work was to develop a separation and purification process of cephamycin C from a fermentation broth produced by cultivations of Streptomyces clavuligerus in aired submerged processes. Extraction and separation processes of cephamycin C were performed by means of an aqueous two-phase system (ATPS) and ionexchange chromatography, respectively. Initially, studies on the stability of cephamycin C were performed in order to allow the establishment of conditions which minimize losses and increase the yield of the global process. In these studies, conditions at pH levels of 2.2, 3.0, 5.0, 6.0, 7.0, 7.6 and 8.7 at a temperature of 20 °C were evaluated. The smallest half-life was of 52.6 hours and was verified for pH 8.7; the longest half-life was of 459 hours for pH 6.0; and for the most acid pH (2.2), half-life was of 118.2 hours. The second step of the work was the study of the separation of cephamycin C and amino acids with the aqueous two-phase system composed by PEG/phosphate. The presence of ornithine, lysine and asparagine amino acids in the fermentation broth, even after the primary separation steps performed by filtration processes consisting of microfiltration and ultrafiltration, is due to the composition of the culture medium which is of complex origin. The experiments were carried out by varying the following parameters: molecular mass of PEG (400, 600, 1000 and 4000), pH (6, 7 and 8), tieline length (TLL 37 and 43) and phase volume ratio (rTLL 0.75, 1.00 and 1.25), in order to enable the determination of the best system for cephamycin C extraction. The best conditions obtained for this process were pH 8, PEG 400, TLL 43 and rTLL 1.00, where the highest partition coefficient, kp of 5.57, was acquired. For the separations of cephamycin C and the amino acids present in the broth, it was possible to verify the following separation efficiencies: 3.4 (ornithine), 6.9 (lysine) and 2.8 (asparagine). The last step of the work showed that it is possible to recover cephamycin C from the PEG phase promoting an even greater purification with the residual amino acids. The ion-exchange chromatography was used to propose so. For this proposal, we used the ion exchange chromatographic technique, with use of anionic resin Amberlite IRA 400. These experiments were performed under temperatures of 20, 25 and 30 °C and pH 2.8 and 6.8. The Amberlite IRA 400 Cl- resin showed affinity for cephamycin C, and in the experiments in fixed bed column, it was possible to separate cephamycin C from PEG, from the phosphate salt and from the amino acids present in the top phase. The results allowed the conclusion that the proposed process is an excellent alternative for the extraction, separation and purification of cephamycin C.